Antimicrobial susceptibility and glycopeptide-resistance of enterococci in vegetables (Italian Journal of Public Health, 2010)
Background: Vancomycin-resistant enterococci (VRE), often responsible for nosocomial infections, havefrequently been isolated from animal and vegetable foods. In our study we evaluated the antibioticsusceptibility of enterococci isolated from eight types of vegetables randomly selected from grocery stores inNaples.Methods: From July to November 2008, we analyzed 150 samples: the bacteria were isolated withstandardized methods and antibiotic susceptibility was determined using the disc diffusion method. Theresistance to vancomycin versus other antibiotics was assessed by the Kappa test.Results: 70% of the samples, mainly parsley (96.2%), showed enterococci. Of these, 59.1% belonged to thespecies Enterococcus faecium. Strains resistant to vancomycin and teicoplanin were isolated respectively in47.6% and 49.5% of the samples: the first one mainly in curly endive (72.7%) and the second one in parsley(76.9%). Almost all the isolated strains showed resistance to methicillin (89%), kanamycin (82%) andcephalothin (68%). The Kappa test showed statistically significant associations between resistance tovancomycin and resistance to teicoplanin, erythromycin, methicillin, tetracycline and chloramphenicol.Conclusions: Because of the possible involvement of food in the transmission of resistant micro-organisms tohuman intestinal microbiota, our data may provide the basis for future studies.
Keywords: enterococci; antimicrobial-resistance; GRE; vegetable